On the Complexity of Brain Disorders: A Symptom-Based Approach - Moustafa, Ahmed A.; Phillips, Joseph; Kéri, Szabolcs; Misiak, Blazej; Frydecka, Dorota (Frontiers in Computational Neuroscience, 2016)
Mounting evidence shows that brain disorders involve multiple and different neural dysfunctions, including regional brain damage, change to cell structure, chemical imbalance, and/or connectivity loss among different brain regions. Understanding the complexity of brain disorders can help us map these neural dysfunctions to different symptom clusters as well as understand subcategories of different brain disorders. Here, we discuss data on the mapping of symptom clusters to different neural dysfunctions using examples from brain disorders such as major depressive disorder, Parkinson’s disease, schizophrenia, PTSD and Alzheimer’s disease. In addition, we discuss data on the similarities of symptoms in different disorders. Importantly, computational modeling work may be able to shed light on plausible links between various symptoms and neural damage in brain disorders.